Experimental analysis of debris distribution of masonry panels subjected to long duration blast loading. (1st January 2017) - Keys, Richard A.; Clubley, Simon K.
Highlights: Experimental trials investigate long duration blast on masonry debris distribution. Various small masonry geometries were tested. Geometry greatly influences breakage patterns and debris distributions. A selection of geometries can be used to represent larger structures. Abstract: Blast loading of structures is a complex system dependent on a vast number of parameters from both the structure and blast wave. Even for the simplest of structures, small changes to its size and shape can have a large effect on the result when subjected to blast; additionally, small changes to the pressure or duration of the blast wave can drastically alter its interaction with a specific structure. This paper, as part of a larger in-depth research study, investigates the breakage patterns and debris distribution of masonry panels subjected to blast loads with a positive phase duration typically exceeding 100 ms. Three experimental trials were conducted, in which ten masonry panels of varying geometries were subjected to blast loads with peak static overpressures of approximately 55 kPa and 110 kPa, with corresponding positive phase durations of 200 ms and 150 ms respectively. All structures underwent total structural failure, followed by significant debris distribution with the results showing structural geometry, blast overpressure and impulse to be the key parameters responsible for the breakage pattern, initial fragmentation and debris distribution respectively.